Discovery of MDV6058 (PF-06952229), a selective and potent TGFβR1 inhibitor: Design, synthesis and optimization. (1st November 2022) - Pujala, Brahmam; Ramachandran, Sreekanth A.; Sonawane, Mukesh; Kamble, Maruti M.; Panpatil, Dayanand; Adhikari, Swati; Soni, Sanjeev; Subbareddy, Venkata; Shinde, Bharat U.; Nayak, Anjan K.; Bansal, Chandni; Gupta, Ashu; et al.
Graphical abstract: Abstract: Compound 1 is a potent TGF-β receptor type-1 (TGFβR1 or ALK5) inhibitor but is metabolically unstable. A solvent-exposed part of this molecule was used to analogue and modulate cell activity, liver microsome stability and mouse pharmacokinetics. The evolution of SAR that led to the selection of 2 (MDV6058 / PF-06952229) as a preclinical lead compound is described.